Future Proofing Study: a cluster randomised controlled trial evaluating the effectiveness of a universal school-based cognitive–behavioural programme for adolescent depression - Maree Teesson; Helen Christensen; Svetha Venkatesh; Aliza Werner-Seidler; Lara Johnston; Bridianne O’Dea; Michelle Torok; Katharine Steinbeck; Raghu Lingam; Andrew Mackinnon; Yael Perry; Kit Huckvale; et al. (BMJ Mental Health)
Background Psychological prevention programmes delivered in schools may reduce symptoms of depression. However, high-quality, large-scale trials are lacking.Objective The aim was to examine whether a digital cognitive–behavioural programme (‘SPARX’), delivered at scale in schools, would reduce depressive symptoms 12 months later.Methods A cluster randomised controlled trial with parallel arms (intervention; control) was conducted in Australian schools, between August 2019 and December 2022. Cluster randomisation occurred at the school level (1:1 allocation). Investigators were blind to group allocation, and outcomes were assessed at baseline, 6 weeks, 6 months (primary outcome only) and 12 months post baseline. The intervention was delivered via smartphone app. Schools were instructed to provide in-class time for intervention completion. The primary outcome was the difference in depressive symptom change from baseline to 12 months between the intervention and control group. Secondary outcomes were change in anxiety, psychological distress and insomnia.Findings 134 schools participated in this study, and baseline data were collected from n=6388 students (n=3266 intervention; n=3122 control). Intent-to-treat analyses showed no difference in depression change between groups from baseline to 12 months, (mean change difference= −0.05, z= −0.32, 95% CI: −0.36 to 0.23, p=0.75). There were no differences on secondary outcomes. Many schools did not provide in-class time for intervention completion, and engagement was low (22% completion rate).Conclusions Scaled delivery of a digital cognitive–behavioural programme did not reduce symptoms of depression, relative to a control group.Clinical implications Given the variability in the engagement with and delivery of the digital universal cognitive–behavioural programme, caution is required prior to scaled delivery of SPARX in school contexts.Trial registration number ACTRN12619000855123.